Leptin deficiency-caused behavioral change – A comparative analysis using EthoVision and DeepLabCut - Bühler, Daniel; Power Guerra, Nicole; Müller, Luisa; Wolkenhauer, Olaf; Düffer, Martin; Vollmar, Brigitte; Kuhla, Angela; Wolfien, Markus (Frontiers in Neuroscience, 2023)
Obese rodents - e.g., the leptin-deficient (ob/ob) mouse - exhibit remarkable behavioral changes and are therefore ideal models for evaluating mental disorders resulting from obesity. In doing so, female as well as male ob/ob mice at 8, 24 and 40 weeks of age underwent two common behavioral tests, namely Open Field test and Elevated Plus Maze, to investigate behavioral alteration in a sex- and age-dependent manner. Accuracy of these tests is often dependent on the observer that can subjectively influence the data. To avoid this bias, mice were tracked with a video system. Video files were further analyzed by the compared use of two software, namely EthoVision (EV) and DeepLabCut (DLC). In DLC a Deep Learning application forms the basis for using artificial intelligence in behavioral research in the future, also with regard to the reduction of animal numbers. After no sex- and partly also no age-related differences were found, comparison revealed that both software lead to almost the same results and are therefore similar in their basic outcomes especially in the determination of velocity and total distance movement. Moreover, we observed additional benefits of DLC compared to EV as it enabled the interpretation of more complex behavior, such as rearing and leaning, in an automated manner. Based on the comparable results from both softwares, our study can serve as a starting point for investigating behavioral alterations in preclinical studies of obesity by using DLC to optimize and probably to predict behavioral observations in the future.